El desempeño metodológico del docente para la atención a niños con manifestaciones de desajustes emocionales y del comportamiento en el centro de educación inicial mundo mágico - Murillo Castro, Mónica Carolina (2017)
The purpose of this research study was to determine the methodological performance of teachers to care for children with manifestations of emotional imbalances and behavior at the initial level. The research was mainly carried out at the "Mundo Mágico" initial education center, an institution that serves children between the ages of 2 and 4 years. Among the methodologies that were used is the observation in class, since they visited the different levels that exist in the Initial Education Center "Mundo Mágico", in times of one-hour class by halls and on different days. Once the classes were observed, interviews were…